Podwichnięcie soczewki jako objaw nabłoniaka rdzeniowego (medulloepithelioma) u 13-letniego chłopca – opis przypadku - Hautz, Wojciech; Chipczyńska, Barbara; Grałek, Mirosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The paper presents the case of the 13 years old boy with the deterioration of vision acuity of the right eye, caused by lens subluxation. The condition was caused by tumour of ciliary body. Additional tests: USG, UBM, CT did not resolve diagnostic doubts. After the biopsy medulloephitelioma was diagnosed and the decision of the eye enucleation was made. Histopathological examination confirmed the diagnosis.